The World Health Organization's Frontline Support to Countries During the COVID-19 Pandemic in 2020 - Coates, Amy; Warren, Kathleen Taylor; Henderson, Corey; McPherson, Michelle; Obubah, Offeibea; Graaff, Peter; Acharya, Shambhu (Frontiers in Public Health, 2022)
The World Health Organization (WHO) declared the SARS-CoV-2 outbreak a Public Health Emergency of International Concern (PHEIC) on 30 January 2020. WHO rapidly scaled up its response including through its 149 country offices to support Member States prepare for and respond to the COVID-19 pandemic. This paper describes the frontline role of the WHO Country Offices (WCOs) and demonstrates that WHO utilized its existing country presence to deliver its global program of work during this unprecedented emergency. Using data collected from the 2020WHO COVID-19 Strategic Preparedness and Response Plan monitoring and evaluation framework assessments, plus data collected in a quantitative survey completed by 149 WCOs during 2020, this paper describes how WHO supported national authorities and partners through leadership, policy dialogue, strategic support, technical assistance, and service delivery, in line with WHO’s current five-year strategic plan, the WHO 13th General Programme of Work 2019-2023. Country level case studies were used to further illustrate actions taken by WCOs. WHO’s achievements notwithstanding, the Organization faced several key challenges in the first year of the response. Recommendations to enhance WHO presence in countries for future emergency prevention, preparedness and response, from several independent reviews, were presented to the World Health Assembly in May 2021 and relevant recommendations are presented in this paper.